PRAKTEK OMNIBUS LAW DALAM PEMBENTUKAN UNDANG-UNDANG KESEHATAN DI INDONESIA - Hutajulu, Maria Margaeta (Ensiklopedia of Journal, 2024)
Abstract: This study examines the practice of the Omnibus Law in the formation of health legislation in Indonesia. The research questions posed are how the Omnibus Law is implemented in Indonesia and its impact on the health sector. The research method used is normative juridical, focusing on the analysis of legislation, official documents, and related legal literature. The findings show that the implementation of the Omnibus Law in Indonesia aims to simplify and expedite the legislative process by consolidating various regulations into a single law. However, in the health sector context, the implementation of the Omnibus Law has various impacts, both positive and negative. Positive impacts include increased efficiency and consistency in health regulations. On the other hand, there are concerns that the rapid and centralized legislative process may overlook public participation and reduce the quality of health policies. This study concludes that although the Omnibus Law has the potential to enhance legislative effectiveness, adequate oversight mechanisms and public participation are necessary to ensure that the resulting health policies truly benefit the public..Keywords: Omnibus Law, Health Legislatio, Public Participation, Regulatory Efficiency.